Triple-band and multiband filters using SIL and MSLOR for wireless communication system. Issue 2 (3rd April 2021) - Ranjan, Prashant
ABSTRACT: This paper presents a compact triple-band and a multiband band-pass filter (BPF) using a stepped impedance line (SIL) and a modified stub-loaded open loop resonator (MSLOR), respectively. The first proposed triple-band BPF used a new technique which involves embedding the stepped impedance line (SIL) between the feed line and the open stubs. Due to this, the proposed filter achieves an ultra wideband (UWB) and two narrow bands with a fractional bandwidth of about 12.85%, 30.38% and 2.6% for use in 4G, WLAN and satellite communication. An UWB is generated with five transmission zeros that increase the high selectivity and avoid the interference between the existing bands. The second proposed filter is triple-band to multiband BPF using MSLOR. This filter achieves five passbands with seven transmission zeros.